Application of carbon nanotubes for removal of copper ion from synthetic water - Kabbashi, Nassereldeen Ahmed; Abdul Karim, Mohamed Ismail; Saeed Mirghaini, Mohamed Elwathig; Yaacob, K. H. K. (Springer, 2008)
The safety and the health of society can be affected by the presence of high concentration of environmental contaminants such as copper ion in wastewater. However, it was found that nanotechnology have shown remarkable results in the removal of the contaminants concentration from water by using nanomaterials. Thus, this study was carried out to evaluate the environmental application of carbon nanotubes for the adsorption experiment for the copper ion removal. The experiment was conducted to identify and determine the factors or the parameters that can influence the adsorption of copper ion such as pH, adsorbent dosage, contact time and agitation speed. The characterization of the carbon nanotubes is conducted by using field emission scanning electron microscope (FESEM). For result analysis, Langmuir and Freundlich Isotherm were used in order to study the kinetics of the adsorption behavior and to determine the adsorption capacity of the carbon nanotube. Regression analysis was used in order to identify the significance of the parameters used to the percentage removal obtained. From this study, it was found that 5 mg, pH 9, 150 rpm, and 80 min are the best conditions for the adsorption of copper ions which give 96.1% of removal.